The Impact of Public Sector Wage Controls in Ontario - Auld, D.A.L.; Wilton, D.A. (Relations industrielles / Industrial Relations, 1987)
This paper seeks to evaluate the effectiveness of Ontario's public sector wage and price controls in ternis of the rate of change in public sector wage